Effect of Massage on the TLR4 Signalling Pathway in Rats with Neuropathic Pain. (17th December 2020) - Wang, Qian; Lin, Jing; Yang, Peng; Liang, Yingye; Lu, Dongming; Wang, Kailong; Gan, Wei; Fu, Jianping; Gan, Zhenbao; Ma, Mingchen; Wu, Pingting; He, Fengshi; et al.
Abstract : This study set out to investigate the effect of massage on the Toll-like receptor 4 (TLR4) signalling pathway in the dorsal root ganglia of rats that had undergone spinal nerve ligation (SNL), with the hypothesis that massage could be used as an analgesic. Forty female SD rats were randomly divided into 5 groups: the control group, sham-operated group, model group, sham massage group, and massage group. There were 8 rats in each group. SNL rat models were established in the model group, sham massage group, and massage group. Rats in the sham-operated group underwent surgery to expose the vertebral nerves, but no further procedures were performed. The control group consisted of intact animals. The rats in the massage group underwent massage using a massage simulation machine once a day for 14 d in succession; the hind limbs of the rats in the sham massage group were gently touched with a cloth bag once a day for 14 continuous days. The rats in the control group, the sham-operated group, and the model group did not receive any intervention and were observed for 14 d. Paw withdrawal thermal latency (PWTL) and paw withdrawal mechanical threshold (PWMT) of rats in each group were detected 1 d before modelling and at 1, 3, 7, and 14 d after modelling. Fourteen days after modelling, the expression levels of TLR4, IRAK1, TRAF6, TNF- α, and IL-6 were detected in all rats. The PWTL and PWMT of SNL rats were decreased, while these parameters were elevated after massage. SNL rats showed higher levels of TLR4, IRAK1, TRAF6, IL-6, and TNF- α, and massage effectively lowered the expression levels of these molecules. Inhibiting activation of the TLR4 signalling pathway, which can reduce the release of inflammatory factors, may be one mechanism by which massage treats neuropathic pain.